2020
DOI: 10.1002/cae.22330
|View full text |Cite
|
Sign up to set email alerts
|

Online coding event as a formative assessment tool in introductory programming and algorithmic courses—An exploration study

Abstract: Information technology is an integral part of current education, even in noncomputer disciplines. As the role of Information technology-based education tools is recognized as significant in the education of millennial learners, there is a development of different types of tools and techniques in education. Usage of such tools in content delivery and assessment has been found to improve student engagement and active learning. When looking for unique tools to practice and assess computer programming and algorith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
1
0
2
Order By: Relevance
“…Recurso didáctico 1) Uso de algún LMS para suministrar contenidos, actividades y evaluaciones 2) Empleo de diagramas de flujo ya sea a través de herramientas especializadas o como parte de la explicación de la lógica de programación 3) Uso directo de algún lenguaje de programación 4) Empleo del teléfono inteligente para ejecutar aplicaciones o accederlas en línea 5) Empleo de software construido ad-hoc para la comprensión y asimilación de la lógica de programación Fuentes que abordan su uso Gajewski, 2018;Viola y Gómez, 2019;Molina et al, 2019;Dhakshina y Dhakshina, 2020;Mehmood et al, 2020;Sharma et al, 2020;Roa y Martínez, 2020;Zang et al, 2020;Cheng et al, 2021;Gajewski, 2018Yi y Lee, 2018;Vasilopoulos y van Schaik, 2018;Jiménez et al, 2019;Solarte y Machuca, 2019;Anderson y González, 2020;Mehmood et al, 2020;Kayaalp y Dinc, 2021;Ochoa y Bedregal, 2022Caceffo et al, 2018Yi y Lee, 2018;Viola y Gómez, 2019;Jiménez et al, 2019;Solarte y Machuca, 2019;Da Costa et al, 2020;Dhayanithia et al, 2021;Susanti et al, 2021;Ochoa y Bedregal, 2022Caceffo et al, 2018Méndez, 2019;Molina et al, 2019;Yücel, 2018;Sharma et al, 2020;Kayaalp y Dinc, 2021;Pérez-Suasnavas y Cela, 2022Yi y Lee, 2018Vasilopoulos y van Schaik, 2018;Méndez, 2019;Hernández et al, 2020;Kazimoglu, 2020;Silva et al, 2020…”
Section: Tabla 3 Los Cinco Recursos Didácticos Más Utilizados Extraíd...unclassified
See 1 more Smart Citation
“…Recurso didáctico 1) Uso de algún LMS para suministrar contenidos, actividades y evaluaciones 2) Empleo de diagramas de flujo ya sea a través de herramientas especializadas o como parte de la explicación de la lógica de programación 3) Uso directo de algún lenguaje de programación 4) Empleo del teléfono inteligente para ejecutar aplicaciones o accederlas en línea 5) Empleo de software construido ad-hoc para la comprensión y asimilación de la lógica de programación Fuentes que abordan su uso Gajewski, 2018;Viola y Gómez, 2019;Molina et al, 2019;Dhakshina y Dhakshina, 2020;Mehmood et al, 2020;Sharma et al, 2020;Roa y Martínez, 2020;Zang et al, 2020;Cheng et al, 2021;Gajewski, 2018Yi y Lee, 2018;Vasilopoulos y van Schaik, 2018;Jiménez et al, 2019;Solarte y Machuca, 2019;Anderson y González, 2020;Mehmood et al, 2020;Kayaalp y Dinc, 2021;Ochoa y Bedregal, 2022Caceffo et al, 2018Yi y Lee, 2018;Viola y Gómez, 2019;Jiménez et al, 2019;Solarte y Machuca, 2019;Da Costa et al, 2020;Dhayanithia et al, 2021;Susanti et al, 2021;Ochoa y Bedregal, 2022Caceffo et al, 2018Méndez, 2019;Molina et al, 2019;Yücel, 2018;Sharma et al, 2020;Kayaalp y Dinc, 2021;Pérez-Suasnavas y Cela, 2022Yi y Lee, 2018Vasilopoulos y van Schaik, 2018;Méndez, 2019;Hernández et al, 2020;Kazimoglu, 2020;Silva et al, 2020…”
Section: Tabla 3 Los Cinco Recursos Didácticos Más Utilizados Extraíd...unclassified
“…Vasilopoulos yvan Schaik, 2018;Molina et al, 2019;Anderson y González, 2020;Dhakshina y Dhakshina, 2020;Hernández et al, 2020;Mehmood et al, 2020; Silva et al, 2020; Zang et al, 2020;Cárdenas et al, 2021;Kayaalp y Dinc, 2021;Ramírez et al, 2022Caceffo et al, 2018 Yücel, 2018;Dhakshina y Dhakshina, 2020;Mehmood et al, 2020;Roa y Martínez, 2020; Sharma et al, 2020;Castro y González, 2021; Susanti et al, 2021;Caceffo et al, 2018Méndez, 2019;Da Costa et al, 2020; Yücel, 2018;Servita y Sánchez, 2020;Correa et al, 2021;Cheng et al, 2021; Susanti et al, 2021 ie revista de investigación educativa de la Rediech vol.15 • 202415 • • e1872 • ISSN: 2448 …”
unclassified
“…Rubio [21] developed a system that predicts future performance according to the student's programming trajectory by applying a machine learning algorithm using the set of data acquired in their own online learning platform, Robomission, and in the Hour of Code challenge. From another perspective, Anitha et al [2] found that student participation and active learning improved by using the online coding event in the content delivery and assessment. They claimed that the usage of online coding platforms is encouraged for introductory programming and algorithmic cources.…”
Section: Programming Education For Novicesmentioning
confidence: 99%